CONCERNS OF PHYSICAL EDUCATION TEACHERS ACCORDING TO PROFESSIONAL DEVELOPMENT CYCLES AND SOCIODEMOGRAPHIC CHARACTERISTICS - Suelen Vicente Vieira; Lucas Jacob Beuttemmuller; Jorge Both (Journal of Physical Education)
ABSTRACT The objective of this study was to analyze concerns of teachers according to professional development cycles and sociodemographic variables. The sample was composed of 92 permanent Physical Education teachers from municipal and state networks of Maringá city (Paraná). For data collection, a sociodemographic questionnaire and the Teacher Concerns Scale were used. For data analysis, Anova for independent samples and the t-test for repeated measures were employed. Results showed smaller concern as to the self dimension compared to the task and task impact dimensions. Moreover, teachers in the renewal cycle were more concerned with the task dimension than those in the consolidation cycle. Assessing sociodemographic variables, teachers working for the state network and female teachers showed a higher index of concern with the “task” dimension, while teachers working at only one school showed greater concern with the self dimension. It is concluded that the concerns present similar behavior with career advancement and that sociodemographic variables have a low impact on teacher concern level.